Cover Image, Volume 29, Issue 9. (1st January 2020) - Anderson, Robert H.; Mori, Shumpei; Spicer, Diane E.; Cheung, Jim W.; Lerman, Bruce B.
Abstract : On the cover : The cover image is based on the Editorial Comment Living anatomy of the pulmonary root by Robert H. Anderson Bsc, MD, PhD (Hon) et al., https://doi.org/10.1111/jce.13691 . [Correction added on December 27, 2019, after first online publication: This additional cover was added to the issue. Late publication date due to systematic error.]